Effect of processing on bioactive compounds of Mandarin and blood orange: a review - Pathaw , P Mariadon Shanlang; Leishangthem, Chinglen; Ripnar, Charis K; Khonglah, Ribhahun (Journal of Postharvest Technology, 2024)
Citrus fruits are a rich source of compounds that influence the sensorial acceptance of juices and other value-added products prepared from it, such as organic acids, phenols and sugars. The strong antioxidant properties are influenced by the presence of bioactive compounds such as flavonoids, phenolic acids, limonoids and adrenergic amines where benzoic and hydroxycinnamic acids form a major part of phenolic compounds while Naringin, Neohesperidin, Narirutin and Hesperidin are present in major quantities. These compounds play an important role in human metabolism through their health-promoting benefits. Given this background, while this review paper acknowledges the research works carried out in this field, it highlights the changes in the bioactive compounds of mandarin and blood oranges when they undergo various processing methods and technologies and at the same time encourages more and rigorous studies especially in the line of blood oranges. It is also worth mentioning here that although the value added products of mandarin and blood oranges exist in the market, yet, scientific research works to determine the optimized process, formulations or venturing technologies for improved processing is scarce.